Prevalence of Hepatitis C Virus and HIV Infection Among Pregnant Women Attending Antenatal Care Clinic in Western Ethiopia - Ejeta, Eyasu; Dabsu, Regea (Frontiers in Medicine, 2019)
Background: Hepatitis C virus (HCV) and HIV infection remain a major public health challenge in Sub-Saharan Africa. The HCV and HIV infection among pregnant women have a serious outcome on maternal and newborn health. There is limited information in this regards in West part of Ethiopia. This study aims to identify the sero- prevalence and predictor factors of HCV and HIV infection among pregnant women attending antenatal care (ANC) in Western Ethiopia Methods: An institutional based cross-sectional study was conducted from July to September, 2014 among 421 pregnant women’s attending ANC services in purposively selected health facilities of western Ethiopia. The HCV and HIV infections were diagnosed by detection antibodies from aseptically collected serum sample. HCV was identified using an enzyme linked immune sorbent assay (ELISA) while HIV infection was tested with rapid HIV tests following the national HIV test algorithm. The pretested and structured questionnaire was used to collect socio-demographic data, and potential predictor factors of HCV and HIV infection. The collected data were analyzed using SPSS version 20.0 statistical software. Result: The overall sero-prevalence of HCV and HIV among the study population was 8.1% and 1.0%, respectively. The prevalence of HCV/HIV co-infection was 0.23% (1/421). Among HIV infected women, the prevalence of HCV infection was 25% (1/4). The risk of HCV infection was significantly low for urban residents (AOR=0.38, 95%CI: 0.16-0.90) and illiterate (AOR= 0.24, 95%CI: 0.06-0.85). However, the history of blood transfusion was significantly increase the risk of HIV infection (AOR = 19.52, 95%CI: 1.80-150.6). Conclusion: Our study confirms public health importance of HCV and HIV infections among pregnant women in the study area. The study suggests need of attention for rural residents and educated segment of the population for HCV prevention, and national blood blank to check HIV test method used for blood transfusion.